2012
DOI: 10.1128/mcb.00394-12
|View full text |Cite
|
Sign up to set email alerts
|

CREB Binding Protein (CBP) Activation Is Required for Luteinizing Hormone Beta Expression and Normal Fertility in Mice

Abstract: Normal function of the hypothalamic-pituitary-gonadal axis is dependent on gonadotropin-releasing hormone (GNRH)-stimulated synthesis and secretion of luteinizing hormone (LH) from the pituitary gonadotroph. While the transcriptional coactivator CREB binding protein (CBP) is known to interact with Egr-1, the major mediator of GNRH action on the Lhb gene, the role of CBP in Lhb gene expression has yet to be characterized. We show that in the L␤T2 gonadotroph cell line, overexpression of CBP augmented the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 58 publications
(87 reference statements)
0
16
0
Order By: Relevance
“…To further investigate the creb KO colon and SI architecture, we explored the relative numbers of Chromogranin A+ve cells, as CREB regulates the ChrA gene 27, 28 and neuroendocrine cell function. 29, 30, 31, 32 However, the number of these cells appeared elevated in the SI and significantly increased in the colon in creb KO mice. Goblet cells and mucin production, as judged by period acid shift (PAS) histochemistry, was more intense in the creb KO colons (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 93%
“…To further investigate the creb KO colon and SI architecture, we explored the relative numbers of Chromogranin A+ve cells, as CREB regulates the ChrA gene 27, 28 and neuroendocrine cell function. 29, 30, 31, 32 However, the number of these cells appeared elevated in the SI and significantly increased in the colon in creb KO mice. Goblet cells and mucin production, as judged by period acid shift (PAS) histochemistry, was more intense in the creb KO colons (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 93%
“…Nephrocystin is involved in spermatogenesis and is required for the differentiation of early elongating spermatids into spermatozoa [21]. Previously, it has been reported that knockdown CREBBP eliminated gnrh; thus, CREBBP may function to regulate the reproductive process [22]. The rest of the proteins identified as hub and key nodes are those previously associated with azoospermia.…”
Section: Resultsmentioning
confidence: 99%
“…2005), and may be necessary to regulate an especially large number of separate processes including LH and FSH synthesis and secretion (Stanislaus et al 1998a), GnRH receptor expression and GnRH receptor desensitization. GnRHR can couple with Gαq/11, GαI, and Gαs (Hawes et al 1993, Stanislaus et al 1998b), and has been shown to exert effects through known insulin targets such as ERK (Bliss et al 2009), PI3K (Navratil et al 2009), FOXO1 (Arriola et al 2012) and CBP (Miller et al 2012). …”
Section: Insulin Regulation Of Neuroendocrine Functionmentioning
confidence: 99%